Study of remote routing strategy in parallel network simulation - Yu CUI; Zhao-xin ZHANG; Hong-li ZHANG; Zhi-hong TIAN (Tongxin xuebao)
The advantages and disadvantages of several remote routing strategies for parallel network simulation were studied，and a new method based on optimize-edge routers was presented.Through converting the original forwarding style of routing IP to routing ID of edge router,the mechanism increased the speed of routing lookup.Also the exploitations of the tree contraction,edge router reduction and assnode reduction in the proposed mechanism effectively decreased the memory cost.Experimental results show 85% reduction in memory use and 75% decrease in time cost for the new routing strategy,comparing with the border-based remote routing strategy in PDNS.